중생 다수성 향미 신품종 ‘효원5호’ - 이영상(Young-Sang Lee); 박용진(Yong-Jin Park); 조유현(Yoo-Hyun Cho); 박소연(So-Yeon Park); 권순욱(Soon-Wook Kwon) (Korean journal of breeding, 2016)
''Hyowon 5’, a new aromatic rice variety with high yield was derived from a cross between 'Dasan’ as a high yield source and ‘IR841-1-1-2’ as a donor for aroma. A general pedigree breeding method was applied to develop Hyowon 5. In F8 generation, a promising line, JS14-12-36-8-5-3-1-1-1, was selected and designated as the name of ‘SP 102’ in 2012. This variety headed on Aug. 14 , which is 3 days later than ‘Hwayoung’ in middle plane. The brown rice of this aromatic variety ‘Hyowon 5’ exhibited 51 odor-active volatiles including a pop corn-flavoring 2-acetyl-1-pyrroline which is exclusively detected in aroma rice varieties. The Culm length and panicle length of this variety was 83.2 cm and 26.4 cm, respectively. This variety has about 14.9 tillers per hill and 124.5 spikelet numbers per panicle. The 1000-grain weight was 20.9 g in brown rice. The yield performance of brown rice was 6.27 MT/ha in local adaptability test.